Implementation of E-learning in EFL Context during COVID-19: Teachers' and Students' Views at One School - Sri Wahyuningsih; Indah Kusumaningrum (Faculty of Language and Literature, University of Surakarta, 2022)
The present study reports the implementation of e-learning in English language teaching during the COVID-19 pandemic at one of the private high schools in Indonesia viewed from teachers' and students' perspectives. Using a qualitative study, the data were garnered through semi-structured interviews with an English teacher, a principal who also teaches English, and students. The result reveals that both teachers and students have the same responses to e-learning practices. There were three stages in implementing e-learning: preparation, implementation, and evaluation. In terms of preparation, the English teacher designed lesson plans as a guideline for learning. In the implementation stage, the English teacher used learning materials from various sources, including textbooks, videos, articles, and other sources on the internet. On the other hand, students reported that English teaching and learning activities in e-learning classes were usually carried out through WhatsApp, Google Classroom, and Zoom meetings. Apart from the advantages of e-learning in English language teaching, some challenges in its practice include the difficulties of operating technical devices for specific teachers, the problems of controlling students during distance learning, etc. Finally, the study's findings promote integrating technology and encouraging teachers' professional development in English language teaching.